2013
DOI: 10.1080/0144929x.2012.708785
|View full text |Cite
|
Sign up to set email alerts
|

Web-enabled wireless technology: an exploratory study of adoption and continued use intentions

Abstract: This study builds upon previous research by comparing and contrasting the decision to adopt wireless technologies with the decision to continue to use wireless technologies. In the context of web-enabled cell phones, we propose, test and compare the predictive ability of two value-based models using a multi-group analysis. The findings suggest that regardless of whether an individual was choosing to adopt or continue to use a web-enabled cell phone, perceived usefulness, enjoyment and perceived fee influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 57 publications
(96 reference statements)
4
46
0
Order By: Relevance
“…Thus the dimensions of the perceived usefulness constructs adopted for this study were significantly predictive of the adoption of social media by the youth (Davis et al, 1992;Lu et al, 2009;Sago, 2013;Lee et al, 2007;Strader et al, 2007). Similarly, the study found the dimensions of perceived ease of use to be significantly predictive of the adoption of social media in line with evidence from extant literature (Burton-Jones and Hubona, 2005;Ilie et al, 2005;Lee et al, 2007;Sago;Setterstrom et al, 2013;Strader et al, 2007;van Slyke, 2007). It is noted that, perceived usefulness and perceived ease of use even though influenced the adoption of technologies such as social media as in this study, with time technologies become very easy to use and their usefulness become obvious.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Thus the dimensions of the perceived usefulness constructs adopted for this study were significantly predictive of the adoption of social media by the youth (Davis et al, 1992;Lu et al, 2009;Sago, 2013;Lee et al, 2007;Strader et al, 2007). Similarly, the study found the dimensions of perceived ease of use to be significantly predictive of the adoption of social media in line with evidence from extant literature (Burton-Jones and Hubona, 2005;Ilie et al, 2005;Lee et al, 2007;Sago;Setterstrom et al, 2013;Strader et al, 2007;van Slyke, 2007). It is noted that, perceived usefulness and perceived ease of use even though influenced the adoption of technologies such as social media as in this study, with time technologies become very easy to use and their usefulness become obvious.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is consistent with most previous studies. For example Setterstrom et al (2013) and Sago (2013) note that people adopt some technology because they are less complex to use. On the other hand, if the technology is complicated and a special skill is needed to operate, people will not use or adopt such technology (Davis et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several theories of continued use describe a set of variables which predict technology adoption, and then include additional variables to the initial model to explain continued use (Setterstrom, Pearson & Orwig, 2013;Kim & Crowston 2011). Others consider continued use in isolation as its own behavior (Bhattacherjee, 2001;Limayem, Cheung & Chan 2003).…”
Section: Theoretical Unificationmentioning
confidence: 99%
“…They found that survey research is prominent and an increasing proportion of that research was conducted using Internet surveys (e.g. Kim et al 2009, Setterstrom et al 2012.…”
Section: Introductionmentioning
confidence: 99%